Reflections on Portuguese humanism at the dawn of the confessional era (Revista Angelus Novus, 2011)
This article seeks to understand the discussed “closing” of the Lusitanian cultural life, experienced at the end of the reign of John III, from an analysis of the concept of “confessionalization process”. Initially, it seeks to characterize the environment experienced by the Portuguese humanism during and especially in the last years of the reign of the Portuguese monarch. Then it accompanies the formation of the concept of “confessionalization process” and offers some critiques that are intended to operationalize it for the study of Portuguese phenomenon. Finally, it seeks to highlight the main features of Portuguese humanism at the beginning of the “confessional age”, from the second half of the sixteenth century, in a critical discussion with a certain bias of Portuguese historiography that posits a radical split between a “literary” strand and a “technical-empirical” one in the bosom of Portuguese humanism.